(untitled) (Journal of the College of Basic Education, 2024)
The idea of the research came to focus on the school of Imam Jaafar al-Sadiq, peace be upon him, which was the school of continuous giving and permanent production in all intellectual, jurisprudential, and ideological fields.Imam Jaafar al-Sadiq, may God bless him and grant him peace, is the sixth of the Twelve Imams among the Jaafari Imam Shiites. He is a descendant of the House of Prophethood and an inheritor of its virtues, virtues, glory and wisdom. He is a spiritual leader who is knowledgeable of the Qur’an and the Sunnah. He is diligent in deriving rulings in the light of the Holy Qur’an. He was in his piety and asceticism, his religion and piety, his knowledge and his jurisprudence. An example to follow. If we mention Imam Jaafar al-Sadiq, may God bless him and grant him peace, we mention the highest honor, the most majestic, and the greatest personality among the pioneers in the history of Islamic thought, whose words had strength and support for the nation, and who became one of the treasures of science and knowledge, then it is obligatory for us to research some of his merits and shed light on his educational and humanitarian positions in... Modest study. Being guided by the educational curriculum of the People of the House, peace be upon them, is one of the basic building blocks of the ladder of doctrinal, intellectual, political and social construction that Islam has approved as a method for correcting belief and regulating.